Food Self‐provisioning in Europe: An Exploration of Sociodemographic Factors in Five Regions1. (5th July 2017) - Vávra, Jan; Megyesi, Boldizsár; Duží, Barbora; Craig, Tony; Klufová, Renata; Lapka, Miloslav; Cudlínová, Eva
Abstract: This article presents the results of an international comparative study on food self‐provisioning, an activity still widespread in the countries of the Global North. We collected the data in a sociological survey done in 2010 as a part of the household energy use research project GILDED. We selected a region with urban and rural areas as a case study in each of the five EU countries, including Scotland, the Netherlands, Germany, the Czech Republic, and Hungary. Our article raises two main research questions: (1) What is the level of food self‐provisioning in the regions? (2) Who participates in it? Additionally, we inquired into the motivations of self‐provisioners using the results of analyses of sociodemographic and food consumption habits for their interpretation. We found that the level of self‐provisioning varies considerably among the regions. Its share ranges from 13 percent in Dutch urban areas to 58 percent in German rural areas. The effects of some sociodemographic and geographic factors differ significantly among the countries. However, we can summarize that living in one's own property, living in a house or in a rural area, having a partner or children, being retired, or having a low income increases the probability of food self‐provisioning.